Al-Mg-Si-Sn-Sc alloy and preparation method thereof

By adding trace Sn and Sc elements to the Al-Mg-Si alloy and adopting a two-stage aging heat treatment process with natural aging and artificial aging, the negative impact of the natural aging of Al-Mg-Si alloy on subsequent artificial aging is solved, and the high-performance hardening and corrosion resistance of the alloy are achieved.

CN117467873BActive Publication Date: 2025-03-11YUNNAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310160842.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-24
Publication Date
2025-03-11
Estimated Expiration
2043-02-24

AI Technical Summary

Technical Problem

Al-Mg-Si alloy will form atomic clusters during the natural aging process, affecting subsequent artificial aging and hardening, resulting in a decrease in peak hardness and an extended peak hardening aging time, which cannot meet industrial needs.

Method used

Using Al-Mg-Si-Sn-Sc alloy and its preparation method, through a dual-stage aging heat treatment process of natural aging and artificial aging, trace amounts of Sn and Sc elements are added to suppress the negative impact of natural aging, and a β-precipitation phase is formed in artificial aging to improve hardening performance.

Benefits of technology

It significantly shortens the peak hardening response time of the alloy, maintains a high peak hardness, improves the corrosion resistance and heat resistance of the alloy, and meets the industry's demand for alloy performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117467873B_ABST
    Figure CN117467873B_ABST
Patent Text Reader

Abstract

The present invention provides an Al‑Mg‑Si‑Sn‑Sc alloy and a preparation method thereof, and belongs to the technical field of non-ferrous metal materials. The present invention adds trace amounts of Sn and Sc elements, wherein Mg and Si mainly form a β″ precipitation phase during artificial aging to harden the alloy; the role of Sn is to recombine with vacancies in the aluminum matrix after solution quenching, inhibit natural aging and extend the room temperature storage time; Sc mainly refines the aluminum matrix grains, and can inhibit the annihilation of vacancies during natural aging, so that even after one week of natural aging, there are still a large number of vacancies in the aluminum matrix, thereby effectively extending the room temperature residence time after quenching, while improving the heat resistance of the alloy; and the movement rate of Sc in the aluminum matrix during artificial aging is relatively slow, which can inhibit the transformation of the precipitation phase and induce the formation of more precipitation phases in the early stage of artificial aging, thereby shortening the peak aging time and improving the strength of the alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nonferrous metal materials, and in particular to an Al-Mg-Si-Sn-Sc alloy and a preparation method thereof. Background Art

[0002] Al-Mg-Si alloy is mainly strengthened by aging heat treatment. Due to its high strength-to-weight ratio and aging hardening rate, as well as good formability and excellent corrosion resistance, it is an important material for various structural parts such as automobiles and high-speed railways.

[0003] The hardness enhancement of Al-Mg-Si alloy is mainly achieved by artificial aging (160-200°C) after rapid quenching from solution treatment (~550°C) to room temperature. During the artificial aging process, a large number of dense nanoscale precipitates are formed in the Al matrix, which effectively strengthens the matrix by preventing dislocation movement. In the actual production process, the alloy will inevitably be parked at room temperature before artificial aging, so a natural aging process will occur, in which atomic clusters will be formed, which usually have a negative impact on subsequent artificial aging hardening, such as reduced peak hardness, prolonged peak hardening aging time, etc., and therefore cannot meet the industrial demand for alloys. Therefore, it is particularly important to provide a new Al-Mg-Si-based alloy that can effectively suppress the negative effects of long-term natural aging after solution treatment and maintain high performance after artificial aging, and its corresponding heat treatment process.

[0004] In order to overcome the negative effects of natural aging of Al-Mg-Si alloy, Chinese patent CN111155002A significantly inhibits the negative effects of natural aging on subsequent paint hardening by adding trace amounts of Sn and optimizing the Sn / (Mg+Si) and Sn / Cu ratios in the alloy, thereby improving the paint hardening ability of Al-Mg-Si alloy after natural aging. After adding Sn, the yield strength of the alloy increased from 160.6MPa to 172.6MPa and the tensile strength increased from 258.5MPa to 261.6MPa after 5 days of natural aging + paint treatment, but the yield strength and tensile strength of the alloy after 14 days of natural aging + paint treatment were only 115.9MPa and 227.3MPa, which was significantly lower than that of five days of natural aging. Summary of the invention

[0005] In view of this, the object of the present invention is to provide an Al-Mg-Si-Sn-Sc alloy and a preparation method thereof. The Al-Mg-Si-Sn-Sc alloy prepared by the present invention using a double-stage aging heat treatment process of natural aging + artificial aging has a significantly shortened peak hardening response time of the alloy after long-term storage at room temperature, and the peak hardness of the alloy does not decrease significantly.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides an Al-Mg-Si-Sn-Sc alloy, comprising the following elements in percentage by mass: Mg: 0.4-0.6%, Si: 0.8-1.2%, Sn: 0.08-0.12%, Sc: 0.08-0.2% and the remainder of Al and unavoidable impurities,

[0008] The Al-Mg-Si-Sn-Sc alloy is prepared by a method comprising the following steps:

[0009] The raw materials and the slag remover are sequentially melted and cast to obtain an ingot;

[0010] The ingot is sequentially subjected to homogenization treatment, heat preservation treatment, hot rolling, cold rolling, solution treatment, quenching, natural aging and artificial aging to obtain the Al-Mg-Si-Sn-Sc alloy.

[0011] Preferably, in the Al-Mg-Si-Sn-Sc alloy, the mass percentage of Mg is 0.5%, the mass percentage of Si is 1%, the mass percentage of Sn is 0.12%, and the mass percentage of Sc is 0.2%.

[0012] Preferably, the natural aging time is 7 days.

[0013] Preferably, the artificial aging temperature is 170-190° C. and the time is 5-8 hours.

[0014] Preferably, the homogenization treatment is carried out at a temperature of 550-560° C. and for a time of 11-12 hours.

[0015] Preferably, the temperature of the heat preservation treatment is 390-400° C., and the time is 20-22 minutes.

[0016] Preferably, the hot rolling is firstly rolled to 8.5-9.5 mm, and then rolled to 3.9-4.1 mm. The cold rolling is sequentially rolled to 3.4-3.6 mm, 2.9-3.1 mm, 2.4-2.6 mm and 1.9-2.1 mm.

[0017] Preferably, the temperature of the solution treatment is 540-550° C., and the time is 60-120 min.

[0018] Preferably, the quenching is water quenching for 3 to 5 seconds.

[0019] The present invention also provides a method for preparing the Al-Mg-Si-Sn-Sc alloy described in the above technical solution, comprising the following steps:

[0020] The raw materials and the slag remover are sequentially melted and cast to obtain an ingot;

[0021] The ingot is sequentially subjected to homogenization treatment, heat preservation treatment, hot rolling, cold rolling, solution treatment, quenching, room temperature aging and artificial aging to obtain the Al-Mg-Si-Sn-Sc alloy.

[0022] The invention provides an Al-Mg-Si-Sn-Sc alloy, comprising the following elements in percentage by mass: 0.4-0.6% Mg, 0.8-1.2% Si, 0.08-0.12% Sn, 0.08-0.2% Sc and the remainder of Al and inevitable impurities. The Al-Mg-Si-Sn-Sc alloy is prepared by a method comprising the following steps: sequentially melting and casting a raw material and a slag remover to obtain an ingot; sequentially performing homogenization treatment, heat preservation treatment, hot rolling, cold rolling, solution treatment, quenching, room temperature aging and artificial aging on the ingot to obtain the Al-Mg-Si-Sn-Sc alloy.

[0023] The present invention adds trace amounts of Sn and Sc elements to the Al-Mg-Si alloy, wherein Mg and Si mainly form a β″ precipitation phase during artificial aging to harden the alloy, the function of Sn is to recombine with vacancies in the aluminum matrix after solution quenching, inhibit natural aging and extend the room temperature storage time, Sc mainly refines the aluminum matrix grains, can inhibit the annihilation of vacancies during natural aging (room temperature storage), so that even after natural aging for one week, there are still a large number of vacancies in the aluminum matrix, thereby effectively extending the room temperature residence time after quenching, and improving the heat resistance of the alloy, and the movement rate of Sc in the aluminum matrix during artificial aging is relatively slow, which can inhibit the transformation of the precipitation phase and induce the formation of more precipitation phases in the early stage of artificial aging, thereby shortening the peak aging time and improving the strength of the alloy, and Sc can also improve the chemical potential of the alloy, thereby improving the corrosion resistance of the alloy, and the co-addition of Sn and Sc is used to inhibit the negative effect of natural aging on subsequent paint hardening, and at the same time improve the corrosion resistance of the alloy, shorten the paint hardening time of the alloy, and improve the over-aging heat resistance of the alloy.

[0024] The present invention also provides a method for preparing the Al-Mg-Si-Sn-Sc alloy described in the above technical solution. The preparation method of the present invention has the following advantages:

[0025] (1) The room temperature residence time after quenching was effectively extended to 1 week. The reason is that the addition of Sn can inhibit the annihilation of vacancies during natural aging (room temperature storage), so that even after 1 week of natural aging, there are still a large number of vacancies in the aluminum matrix.

[0026] (2) The prepared Al-Mg-Si-Sn-Sc alloy was stored at room temperature for 1 week and then artificially aged at (170-190)°C. Under the premise of basically maintaining the peak hardness of the material, the peak aging response speed was greatly shortened to 5-8h. The reason is that the addition of Sc can induce the formation of more precipitation phases in the early stage of artificial aging, refine the collective grains, and thus shorten the peak aging time.

[0027] (3) After the designed alloy was stored at room temperature for 1 week, it was artificially aged at (170-190)℃ / (5-8)h, and the electrochemical corrosion performance of the alloy was greatly improved. The reason is that Sc can increase the chemical potential of the alloy and improve the corrosion resistance of the alloy.

[0028] (4) After the designed alloy was stored at room temperature for one week, it was artificially aged at (170-190)℃ / (5-8)h, and the heat resistance of the alloy was greatly improved. The reason is that Sc can inhibit the transformation of the peak failure precipitation phase. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is the hardness curve of the alloys prepared in Example 1 and Comparative Examples 1-2;

[0030] Figure 2 The peak hardness curves of the alloys obtained after different room temperature natural aging in Example 1;

[0031] Figure 3 These are electrochemical test diagrams of the alloys prepared in Example 1 and Comparative Examples 1-2, where a is the Nyquist diagram and b is the Bode diagram. DETAILED DESCRIPTION

[0032] The present invention provides an Al-Mg-Si-Sn-Sc alloy, comprising the following elements in percentage by mass: Mg: 0.4-0.6%, Si: 0.8-1.2%, Sn: 0.08-0.12%, Sc: 0.08-0.2% and the remainder of Al and unavoidable impurities,

[0033] The Al-Mg-Si-Sn-Sc alloy is prepared by a method comprising the following steps:

[0034] The raw materials and the slag remover are sequentially melted and cast to obtain an ingot;

[0035] The ingot is subjected to homogenization treatment, heat preservation treatment, hot rolling, cold rolling, solution treatment, quenching, natural aging (room temperature aging) and artificial aging in sequence to obtain the Al-Mg-Si-Sn-Sc alloy.

[0036] In the present invention, the mass percentage of Mg in the Al-Mg-Si-Sn-Sc alloy is preferably 0.5%, the mass percentage of Si is preferably 1%, the mass percentage of Sn is preferably 0.12%, and the mass percentage of Sc is preferably 0.2%.

[0037] In the present invention, the Mg and Si mainly form β″ precipitation phase during artificial aging to harden the alloy, the Sn is used to recombine with vacancies in the aluminum matrix after solution quenching to inhibit natural aging and extend the room temperature storage time, and the Sc is mainly used to refine the aluminum matrix grains and improve the strength, heat resistance and corrosion resistance of the alloy.

[0038] The invention melts and casts the raw material and the slag remover in sequence to obtain an ingot.

[0039] In the present invention, the raw materials preferably include pure Mg, Al-Si alloy, Al-Si alloy, Al-Sn intermediate, Al-Sc intermediate alloy and pure Al.

[0040] In the present invention, the mass fraction of Si in the Al-Si alloy is preferably 20%.

[0041] In the present invention, the mass fraction of Sn in the Al-Sn master alloy is preferably 18%.

[0042] In the present invention, the mass fraction of Sc in the Al-Sc master alloy is preferably 2%.

[0043] In the present invention, the deslagging agent is preferably hexachloroethane, and the mass of the deslagging agent is preferably 0.3% of the mass of the raw material.

[0044] In the present invention, the melting preferably includes the following steps: adding pure aluminum and Al-Sc master alloy to a crucible furnace heated to 590-600°C and keeping the temperature for 50-60 minutes to completely dissolve the Sc element, then heating to 790-800°C and keeping the temperature for 9-10 minutes to completely dissolve the alloy, then adding pure Al, pure Mg, Al-Si alloy and Al-Sn master alloy, stirring evenly with a graphite rod, keeping the temperature for 14-16 minutes, then adding a slag remover, stirring evenly and removing impurities, and finally cooling to 750-760°C and keeping the temperature for 10-12 minutes.

[0045] In the present invention, the casting is preferably performed by directly casting into a flat ingot using a water-cooled mold.

[0046] After obtaining the ingot, the present invention sequentially performs homogenization treatment, heat preservation treatment, hot rolling, cold rolling, solution treatment, quenching, room temperature aging and artificial aging on the ingot to obtain the Al-Mg-Si-Sn-Sc alloy.

[0047] In the present invention, the temperature of the homogenization treatment is preferably 550-560° C., and the time is preferably 11-12 hours.

[0048] In the present invention, the homogenization treatment is preferably performed in a tube furnace.

[0049] In the present invention, the temperature of the heat preservation treatment is preferably 390-400° C., and the time is preferably 20-22 minutes.

[0050] In the present invention, the hot rolling is preferably firstly rolled to 8.5-9.5 mm, and then rolled to 3.9-4.1 mm. The cold rolling is preferably sequentially rolled to 3.4-3.6 mm, 2.9-3.1 mm, 2.4-2.6 mm and 1.9-2.1 mm.

[0051] In the present invention, after the hot rolling is completed, air cooling is preferably also included.

[0052] In the present invention, the temperature of the solution treatment is preferably 540-550° C., and the time is preferably 60-120 min.

[0053] In the present invention, the quenching is preferably water quenching, and the time is preferably 3 to 5 seconds.

[0054] After the quenching is completed, the present invention preferably further comprises natural air drying followed by natural aging.

[0055] In the present invention, the natural aging (NA) time is preferably 7 days. The addition of Sn can inhibit the annihilation of vacancies during the natural aging (room temperature storage), so that a large number of vacancies still exist in the aluminum matrix even after 1 week of natural aging.

[0056] In the present invention, the temperature of the artificial aging (AA) is preferably 170-190° C., and the time is preferably 5-8 h. During the artificial aging process, the movement rate of the Sc in the aluminum matrix is ​​relatively slow, which can inhibit the transformation of the precipitated phase, induce the formation of more precipitated phases in the early stage of artificial aging, and refine the collective grains. Under the premise of basically maintaining the peak hardness of the material, the peak aging response speed can be greatly shortened, thereby shortening the peak aging time and improving the heat resistance of the alloy.

[0057] The present invention also provides a method for preparing the Al-Mg-Si-Sn-Sc alloy described in the above technical solution, comprising the following steps:

[0058] The raw materials and the slag remover are sequentially melted and cast to obtain an ingot;

[0059] The ingot is sequentially subjected to homogenization treatment, heat preservation treatment, hot rolling, cold rolling, solution treatment, quenching, room temperature aging and artificial aging to obtain the Al-Mg-Si-Sn-Sc alloy.

[0060] In the present invention, the preparation method of the Al-Mg-Si-Sn-Sc alloy is preferably consistent with the above-mentioned solution, which will not be described in detail here.

[0061] In order to further illustrate the present invention, the Al-Mg-Si-Sn-Sc alloy and the preparation method thereof provided by the present invention are described in detail below in conjunction with examples, but they should not be construed as limiting the scope of protection of the present invention.

[0062] Example 1

[0063] High-strength and corrosion-resistant aluminum alloy Al-Mg-Si-Sn-Sc. The preparation method of the high-strength and corrosion-resistant aluminum alloy comprises the following steps:

[0064] (1) First, prepare the raw materials with the corresponding chemical composition ratio: the alloy composition (by mass percentage) includes: Mg: 0.5%, Si: 1.0%, Sn: 0.12%, Sc: 0.2%. First, prepare pure Mg, Al-Si alloy with a mass fraction of 20%, Al-Sn master alloy with a mass fraction of 18%, Al-Sc master alloy with a mass fraction of 2%, and pure Al for use;

[0065] (2) adding pure aluminum and Al-Sc master alloy to a crucible furnace heated to 600° C. and keeping the temperature for 50 minutes, then heating to 800° C. and keeping the temperature for about 9 minutes until the alloy is completely dissolved, then adding pure Al, pure Mg and 20% by mass of Al-Si alloy and 18% by mass of Al-Sn master alloy, stirring evenly with a graphite rod, keeping the temperature for 16 minutes, then adding 0.3wt% of hexachloroethane slag remover, stirring evenly and removing impurities, finally cooling to 60° C. and keeping the temperature for 12 minutes, and then directly casting into a flat ingot with a water-cooled mold;

[0066] (3) the alloy ingot was placed in a tube furnace for homogenization at 560°C for 12 hours, then kept at 400°C for 22 minutes, hot rolled to 9.5 mm and then to 4.1 mm, air-cooled, and then cold rolled at room temperature to 3.6 mm, 3.1 mm, 2.6 mm, and 2.0 mm;

[0067] (4) placing the obtained Al-Mg-Si-Sn-Sc alloy into a tube furnace at 550° C. for solution treatment for 60 minutes;

[0068] (5) After the solution is completed, take out the alloy and place it in water to quench it to room temperature. The quenching transfer time is 5 seconds:

[0069] (6) After quenching, the air-dried alloy is placed at room temperature:

[0070] (7) After being naturally aged at room temperature for 1, 7, 14 and 30 days, the alloys were placed in a tube furnace at 180°C for artificial aging for different times.

[0071] Comparative Example 1

[0072] The same as Example 1, the only difference is that Sc is replaced by Al.

[0073] Comparative Example 2

[0074] The same as Example 1, the only difference is that natural aging at room temperature is not performed.

[0075] Figure 1 The hardness curves of the alloys obtained in Example 1 and Comparative Examples 1 to 2 show that the present invention can shorten the paint hardening time of the alloy and improve the over-aging heat resistance of the alloy. The main reason is that the addition of Sc can refine the aluminum matrix grains and improve the strength of the alloy. In addition, Sc can improve the corrosion resistance of the matrix. At the same time, the movement rate of Sc in the aluminum matrix during artificial aging is relatively slow, which can inhibit the transformation of the precipitated phase and improve the heat resistance of the alloy.

[0076] Figure 2 This is the peak hardness curve of the alloy obtained after different room temperature natural aging in Example 1. It can be seen that the peak hardness of the alloy is the largest when the NA time is 7 days.

[0077] Figure 3 These are the electrochemical test diagrams of the alloys prepared in Example 1 and Comparative Examples 1 to 2, wherein a is the Nyquist diagram and b is the Bode diagram. It can be seen that the present invention utilizes the co-addition of Sn and Sc to suppress the negative effects of natural aging on subsequent paint hardening, while improving the corrosion resistance of the alloy.

[0078] Figures 1 to 3 In the table, NA means natural aging and AA means artificial aging.

[0079] Comparative Example 3

[0080] High-strength and corrosion-resistant aluminum alloy Al-Mg-Si-Sn-Sc. The preparation method of the high-strength and corrosion-resistant aluminum alloy comprises the following steps:

[0081] (1) First, prepare the raw materials with the corresponding chemical composition ratio: the alloy composition (by mass percentage) includes: Mg: 0.4%, Si: 1.2%, Sn: 0.1%, Sc: 0.1%. First, prepare pure Mg, Al-Si alloy with a mass fraction of 20%, Al-Sn master alloy with a mass fraction of 18%, Al-Sc master alloy with a mass fraction of 2%, and pure Al for use;

[0082] (2) adding pure aluminum and Al-Sc master alloy to a crucible furnace heated to 590° C. and keeping the temperature for 60 minutes, then heating to 790° C. and keeping the temperature for about 10 minutes until the alloy is completely dissolved, then adding pure Al, pure Mg and 20% by mass of Al-Si alloy and 18% by mass of Al-Sn master alloy, stirring evenly with a graphite rod, keeping the temperature for 14 minutes, then adding 0.3 wt % of the raw material hexachloroethane slag remover, stirring evenly and removing impurities, finally cooling to 750° C. and keeping the temperature for 10 minutes, and then directly casting into a flat ingot using a water-cooled mold;

[0083] (3) the alloy ingot was placed in a tube furnace for homogenization at 550°C for 11 hours, then kept at 390°C for 20 minutes, hot rolled to 8.5 mm and then to 3.9 mm, air-cooled, and then cold rolled at room temperature to 3.4 mm, 2.9 mm, 2.4 mm, and 2.0 mm;

[0084] (4) placing the obtained Al-Mg-Si-Sn-Sc alloy into a tube furnace at 540° C. and subjecting it to solution treatment for 60 minutes;

[0085] (5) After the solution treatment is completed, the alloy is taken out and placed in water to quench to room temperature. The quenching transfer time is 3 seconds:

[0086] (6) After quenching, the air-dried alloy is placed at room temperature:

[0087] (7) After being naturally aged at room temperature for 7 days, the alloy was placed in a tube furnace at 170°C for artificial aging for 5 hours.

[0088] Comparative Example 4

[0089] High-strength and corrosion-resistant aluminum alloy: Al-Mg-Si-Sn-Sc. The preparation method of the high-strength and corrosion-resistant aluminum alloy comprises the following steps:

[0090] (1) First, prepare the raw materials with the corresponding chemical composition ratio: the alloy composition (by mass percentage) includes: Mg: 0.4%, Si: 1.2%, Sn: 0.1%, Sc: 0.1%. First, prepare pure Mg, Al-Si alloy with a mass fraction of 20%, Al-Sn master alloy with a mass fraction of 18%, Al-Sc master alloy with a mass fraction of 2%, and pure Al for use;

[0091] (2) adding pure aluminum and Al-Sc master alloy to a crucible furnace heated to 590° C. and keeping the temperature for 60 minutes, then heating to 790° C. and keeping the temperature for about 10 minutes until the alloy is completely dissolved, then adding pure Al, pure Mg and 20% by mass of Al-Si alloy and 18% by mass of Al-Sn master alloy, stirring evenly with a graphite rod, keeping the temperature for 14 minutes, then adding 0.3 wt % of the raw material hexachloroethane slag remover, stirring evenly and removing impurities, finally cooling to 750° C. and keeping the temperature for 10 minutes, and then directly casting into a flat ingot using a water-cooled mold;

[0092] (3) the alloy ingot was placed in a tube furnace for homogenization at 550°C for 11 hours, then kept at 390°C for 20 minutes, hot rolled to 8.5 mm and then to 3.9 mm, air-cooled, and then cold rolled at room temperature to 3.4 mm, 2.9 mm, 2.4 mm, and 2.0 mm;

[0093] (4) placing the obtained Al-Mg-Si-Sn-Sc alloy into a tube furnace at 540° C. for solution treatment for 120 minutes;

[0094] (5) After the solution is completed, take out the alloy and place it in water to quench it to room temperature. The quenching transfer time is 3 seconds:

[0095] (6) After quenching, the air-dried alloy is placed at room temperature:

[0096] (7) After being naturally aged at room temperature for 7 days, the alloy was placed in a tube furnace at 180°C for artificial aging for 7 hours.

[0097] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. An Al-Mg-Si-Sn-Sc alloy, characterized in that: The following elements are included in mass percentage: Mg: 0.4-0.6%, Si: 0.8-1.2%, Sn: 0.08-0.12%, Sc: 0.08-0.2% and the balance of Al and unavoidable impurities, The Al-Mg-Si-Sn-Sc alloy is prepared by a method comprising the following steps: The raw materials and the slag remover are sequentially melted and cast to obtain an ingot; The ingot is subjected to homogenization treatment, heat preservation treatment, hot rolling, cold rolling, solution treatment, quenching, natural aging and artificial aging in sequence to obtain the Al-Mg-Si-Sn-Sc alloy; the natural aging time is 7 days.

2. The Al-Mg-Si-Sn-Sc alloy according to claim 1, characterized in that: The mass percentage of Mg in the Al-Mg-Si-Sn-Sc alloy is 0.5%, the mass percentage of Si is 1%, the mass percentage of Sn is 0.12%, and the mass percentage of Sc is 0.2%.

3. The Al-Mg-Si-Sn-Sc alloy according to claim 1, characterized in that: The temperature of the artificial aging is 170-190° C., and the time is 5-8 hours.

4. The Al-Mg-Si-Sn-Sc alloy according to claim 1, characterized in that: The temperature of the homogenization treatment is 550-560° C. and the time is 11-12 hours.

5. The Al-Mg-Si-Sn-Sc alloy according to claim 1, characterized in that: The temperature of the heat preservation treatment is 390-400° C., and the time is 20-22 minutes.

6. The Al-Mg-Si-Sn-Sc alloy according to claim 1, characterized in that: The hot rolling is firstly rolled to 8.5-9.5 mm, and then rolled to 3.9-4.1 mm. The cold rolling is sequentially rolled to 3.4-3.6 mm, 2.9-3.1 mm, 2.4-2.6 mm and 1.9-2.1 mm.

7. The Al-Mg-Si-Sn-Sc alloy according to claim 1, characterized in that: The temperature of the solution treatment is 540-550° C. and the time is 60-120 min.

8. The Al-Mg-Si-Sn-Sc alloy according to claim 1, characterized in that: The quenching is water quenching, and the time is 3 to 5 seconds.

9. The method for preparing the Al-Mg-Si-Sn-Sc alloy according to any one of claims 1 to 8, characterized in that: The following steps are involved: The raw materials and the slag remover are sequentially melted and cast to obtain an ingot; The ingot is sequentially subjected to homogenization treatment, heat preservation treatment, hot rolling, cold rolling, solution treatment, quenching, room temperature aging and artificial aging to obtain the Al-Mg-Si-Sn-Sc alloy.

Citation Information

Patent Citations

  • Vehicle body aluminum-magnesium-silicon alloy reducing negative effect of natural aging and preparation method

    CN111155002A

  • High-strength aluminum alloy plate

    CN107532247A